METHODS OF DEVELOPING STUDENTS' SOCIO-CULTURAL COMPETENCE IN ENGLISH THROUGH AUTHENTIC VIDEO MATERIALS IN OFFLINE AND ONLINE EDUCATION SETTINGS - Usmanova K.Kh (The latest news and research in education, 2025)
This article explores effective methods for developing students' socio-cultural competence in English through the use of authentic video materials in both offline and online education settings. Socio-cultural competence is essential for learners of English as a foreign language (EFL), enabling them to understand and navigate cultural contexts, norms, and practices of English-speaking communities. This paper discusses the role of authentic video materials, defines socio-cultural competence, reviews pedagogical methods for integrating videos into EFL instruction, and examines the advantages of both offline and online approaches. Key strategies include task-based learning, critical thinking development, and collaborative activities, which together enhance learners' ability to interact meaningfully in diverse social and cultural contexts. The study concludes by providing practical recommendations for teachers aiming to incorporate these resources into their teaching practices.